The insulator protein Suppressor of Hairy wing is required for proper ring canal development during oogenesis in Drosophila. - Hsu, S.J.; Plata, M.P.; Ernest, B.; Asgarifar, S.; Labrador, M. (Developmental Biology, 2015)
Chromatin insulators orchestrate gene transcription during embryo development and cell differentiation by stabilizing interactions between distant genomic sites. Mutations in genes encoding insulator proteins are generally lethal, making in vivo functional analyses of insulator proteins difficult. In Drosophila, however, mutations in the gene encoding the Suppressor of Hairy wing insulator protein [Su(Hw)] are viable and female sterile, providing an opportunity to study insulator function during oocyte development. Whereas previous reports suggest that the function of Su(Hw) in oogenesis is independent of its insulator activity, many aspects of the role of Su(Hw) in Drosophila oogenesis remain unexplored. Here we show that mutations in su(Hw) result in smaller ring canal lumens and smaller outer ring diameters, which likely obstruct molecular and vesicle passage from nurse cells to the oocyte. Fluorescence microscopy reveals that lack of Su(Hw) leads to excess accumulation of Kelch (Kel) and Filament-actin (F-actin) proteins in the ring canal structures of developing egg chambers. Furthermore, we found that misexpression of the Src oncogene at 64B (Src64B) may cause ring canal development defects as microarray analysis and real-time RT-PCR revealed there is a three fold decrease in Src64B expression in su(Hw) mutant ovaries. Restoration of Src64B expression in su(Hw) mutant female germ cells rescued the ring phenotype but did not restore fertility. We conclude that loss of su(Hw) affects expression of many oogenesis related genes and down-regulates Src64B, resulting in ring canal defects potentially contributing to obstruction of molecular flow and an eventual failure of egg chamber organization.